Sex Differences in Protective Effect of Recombinant Human Erythropoietin Against Cisplatin-induced Nephrotoxicity in Rats (Iranian Journal of Kidney Diseases, 2013)
Introduction. The protective role of recombinant human erythropoietin (RHE) against cisplatin-induced nephrotoxicity has been reported, but the role of sex differences is not clearly known. The aim of this study was to determine the sex-based difference in the protective effect of RHE against cisplatin-induced nephrotoxicity. Materials and Methods. Thirty-three Wistar rats were divided into 6 groups. According to protocol l, male and female rats were treated with RHE (100 IU/kg/d) for 3 days and then received a single dose of cisplatin (7 mg/kg). According to protocol 2, the rats received the same single dose of cisplatin and then were treated with RHE for 7 days. Two other groups of male and female  rats received a similar regimen of protocol 2 except for saline instead of RHE. All the animals were sacrificed 1 week after cisplatin administration. Results. All of the experimental animals experienced weight loss. The percentage change of weight in male rats with protocol 1 was significantly less than that in male rats in protocol 2 and control groups. However, in female groups, the percentage of change in weights was slightly higher with protocol 2 than with protocol 1 and control treatment. Administration of RHE significantly decreased changes in serum creatinine, BUN, and malondialdehyde levels in male rats, but not in females. No significant difference was observed in serum nitrite level, kidney weight, and kidney damage score between the groups. Conclusions. This study suggested that erythropoietin may lead to different responses against cisplatin-induced nephrotoxicity in male and female rats.